THE INFLUENCE OF CULTURE AND ENVIRONMENT ON PERTUKARAN MAHASISWA MERDEKA (PMM) UNIVERSITAS MUHAMMADIYAH TANGERANG ON LEARNING INDONESIAN - Masyarah Melgia, Cut Alia; Syahrin, Alfi (JURNAL KONFIKS, 2025)
PeProgram Pertukaran Mahasiswa Merdeka (PMM) offers students the opportunity to study at other universities across Indonesia, enriching their academic and cultural experiences. Exposure to different cultural and environmental contexts may influence the learning process, particularly in mastering the Indonesian language. This study aims to examine the influence of cultural and environmental factors on the academic performance of PMM students at Universitas Muhammadiyah Tangerang, employing a quantitative causal approach. The findings reveal that cultural differences significantly impact learning outcomes due to disparities between students’ home cultures and the host institution’s cultural context. However, environmental factors were found to have no significant effect, as both the sending and receiving institutions provide equally supportive learning environments with qualified educators. Theoretically, this study contributes to a deeper understanding of the role of cultural variables in shaping learning behavior within multilingual and multicultural contexts. Practically, the findings highlight the importance of cultural adaptation programs in student exchange initiatives to enhance academic integration and learning outcomes. Therefore, universities are encouraged to develop orientation and support strategies that are responsive to the cultural diversity of their students.